Eight elements of an effective takeoff - McGinnis, P. M. (2000)
The takeoff is the most important phase of the pole vault. The takeoff phase begins when the vaulter's takeoff foot strikes the runway at the end of his last step, and it ends at the instant of takeoff, the instant when the takeoff foot is no longer in contact with the runway. The vaulter's actions during the takeoff greatly affect the vaulter's actions during subsequent phases of the vault and ultimately affect the height achieved by the vaulter. The importance of the takeoff phase may be best illustrated by examining the factors that determine pole vault performance. Mechanically, work and energy principles can be used to derive an equation for the maximum height achieved by a vaulter. presented at the NATIONAL POLE VAULT SUMMIT January 21-22, 2000 • Reno, Nevada